TRANSFORMASI PEMBELAJARAN IPAS MELALUI STEM-ESD DALAM MEMBANGUN SUSTAINABILITY CONSCIOUSNESS SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW TAHUN 2021–2026 - Nur Malihah, Chelly; Dudu Suhandi Saputra; Yuyu Yuliati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The environmental crisis, climate change, energy depletion, and unsustainable human behavior have become global challenges requiring educational transformation from an early age. This study aims to analyze the transformation of Integrated Science and Social Studies (IPAS) learning through the STEM-ESD approach in developing sustainability consciousness among elementary school students. This research employed a Systematic Literature Review (SLR) by reviewing scientific articles published between 2021 and 2026 from Google Scholar, ERIC, DOAJ, ScienceDirect, and reputable journals. The findings indicate that STEM-ESD effectively integrates science, technology, engineering, mathematics, and sustainability principles into contextual and project-based learning. This approach improves students' sustainability consciousness through three dimensions: cognitive, affective, and behavioral aspects. Students become more capable of understanding environmental issues, developing environmental awareness, and implementing sustainable behaviors in daily life. However, several challenges remain, including teachers’ readiness, learning resources, and the consistency of sustainability-oriented learning implementation in elementary schools. Therefore, STEM-ESD serves as an innovative educational approach that supports 21st-century competencies and promotes sustainable development goals through meaningful and transformative learning experiences.